Agents that increase the permeability of the outer membrane. - Vaara, M (1992)
The outer membrane of gram-negative bacteria provides the cell with an effective permeability barrier against external noxious agents, including antibiotics, but is itself a target for antibacterial agents such as polycations and chelators. Both groups of agents weaken the molecular interactions of the lipopolysaccharide constituent of the outer membrane. Various polycations are able, at least under certain conditions, to bind to the anionic sites of lipopolysaccharide. Many of these disorganize and cross the outer membrane and render it permeable to drugs which permeate the intact membrane very poorly. These polycations include polymyxins and their derivatives, protamine, polymers of basic amino acids, compound 48/80, insect cecropins, reptilian magainins, various cationic leukocyte peptides (defensins, bactenecins, bactericidal/permeability-increasing protein, and others), aminoglycosides, and many more. However, the cationic character is not the sole determinant required for the permeabilizing activity, and therefore some of the agents are much more effective permeabilizers than others. They are useful tools in studies in which the poor permeability of the outer membrane poses problems. Some of them undoubtedly have a role as natural antibiotic substances, and they or their derivatives might have some potential as pharmaceutical agents in antibacterial therapy as well. Also, chelators (such as EDTA, nitrilotriacetic acid, and sodium hexametaphosphate), which disintegrate the outer membrane by removing Mg2+ and Ca2+, are effective and valuable permeabilizers.